Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/hed.21274
|View full text |Cite
|
Sign up to set email alerts
|

Treatment guideline for hemangiomas and vascular malformations of the head and neck

Abstract: Abstract:Vascular anomalies are among the most common congenital and neonatal dysmorphogenesis, which are separated into hemangiomas and vascular malformations. They can occur in various areas throughout the body, with 60% being located in the head and neck. The true mechanism of pathogenesis of vascular anomalies is still unclear. Various treatment methods have been reported, and there are still controversies over the selection of different treatment modalities. Based on the clinical and basic research and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 42 publications
0
103
0
14
Order By: Relevance
“…Pirmiausia taikomas aktyvus paciento sekimas ir konservatyvus gydymas, ir tik retais atvejais pirmo pasirinkimo gydymas yra chirurginis [8].…”
Section: Galvos Ir Kaklo Srities Hemangiomų Gydymo Būdų Apžvalgaunclassified
See 1 more Smart Citation
“…Pirmiausia taikomas aktyvus paciento sekimas ir konservatyvus gydymas, ir tik retais atvejais pirmo pasirinkimo gydymas yra chirurginis [8].…”
Section: Galvos Ir Kaklo Srities Hemangiomų Gydymo Būdų Apžvalgaunclassified
“…[9]. Tyrimai rodo, kad geriamasis prednizolonas yra efektyvesnis nei metilprednizolonas [8]. Dažniausiai prednizolono skiriama gerti 3-5 mg/kg kas antrą rytą nuo 6 iki 8 savaičių; po to vaisto dozė palaipsniui mažinama dvi-tris savaites -iki visiško vaisto nutraukimo.…”
Section: Galvos Ir Kaklo Srities Hemangiomų Gydymo Būdų Apžvalgaunclassified
“…Тактика «активного невмешательства» допусти-ма в тех случаях, когда течение ИГ стабильно, они не вызывают обструкцию жизненно важных орга-нов, не несут угрозы нарушения витальных функ-ций, локализуются не на лице и не приводят к фор-мированию грубого косметического дефекта [12].…”
Section: принципы терапииunclassified
“…склерозирование; 2. лазерохирургия; 3. криотерапия; 4. хирургическое иссечение. При выборе метода лечения необходимо оцени-вать его эффективность и побочные эффекты [12].…”
Section: к хирургическим методам лечения иг относятсяunclassified
“…Other predisposing factors are: light colored skin, premature births, and low birth weight. 7 Hemangiomas generally occur sporadically, however due to families which show multiple occurrences in subsequent generations, it has been suggested that there may be an autosomal dominant inheritance pattern, specifically a loss of heterozygosity on chromosome 5q31-33.5 20% of hemangiomas can be seen at birth, and most times can be visualized in utero, and are termed congenital hemangiomas (CH). CH are fully formed before birth and unlike infantile hemangiomas (IH) do not proliferate after birth but only have stages of involution.…”
Section: Classificationmentioning
confidence: 99%